Surface-treated steel sheet
By forming a chemical conversion film containing Zr, V, P and Co on the plating layer of the surface-treated steel plate, the problem of discoloration of the surface-treated steel plate during condensation is solved, and corrosion resistance, adhesiveness and black degeneration resistance are improved, achieving better surface treatment effect.
Patent Information
- Application Number
- CN202380061759.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing surface-treated steel plates are prone to condensation and discoloration when the surface is condensed, which affects the appearance and is difficult to obtain excellent corrosion resistance, adhesiveness and black degeneration resistance at the same time.
A plating layer formed on the base material steel plate is used, and a chemical conversion film containing Zr, V, P and Co, as well as an acrylic resin are formed on the plating layer. The adhesion amount and component ratio of the chemical conversion film are controlled to optimize the chemical composition of the plating layer and the structure of the film.
It realizes excellent corrosion resistance, adhesion, black resistance and condensation discoloration resistance of surface-treated steel plates, and improves the performance and appearance quality of the product.
Smart Images

Figure CN119768556A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a surface-treated steel plate having a coating layer and a chemical conversion film disposed on the surface. Background Art
[0002] The surface treated steel sheet has a base steel sheet, a plating layer formed on the base steel sheet, and a coating formed on the plating layer. The surface treated steel sheet is widely used in building materials, automobiles, and home appliances. The surface treated steel sheet improves corrosion resistance by using the plating layer and the coating.
[0003] As a coating for improving the corrosion resistance of the surface-treated steel sheet, a coating formed by a chemical conversion treatment such as chromate treatment or phosphate treatment, a coating formed by an inorganic material, an organic resin coating, and a coating formed by an inorganic material and an organic resin have been proposed.
[0004] For example, a coating formed of an inorganic material is disclosed in Japanese Patent Publication No. 2002-030460 (Patent Document 1) and International Publication No. 2007 / 123276 (Patent Document 2). In Patent Document 1, a metal surface treatment agent containing a vanadium compound and a metal compound containing at least one metal selected from zirconium, titanium, molybdenum, tungsten, manganese and cerium is proposed. In addition, in Patent Document 2, a composite coating treatment of zinc-containing plated steel using a treatment solution containing an alkaline zirconium compound, an oxygen-containing vanadium compound, a phosphate compound, a cobalt compound, an organic acid and water is proposed.
[0005] Organic resin coatings are disclosed in International Publication No. 2007 / 069783 (Patent Document 3) and International Publication No. 2009 / 004684 (Patent Document 4). Patent Document 3 proposes an organic resin coating formed by a surface treatment agent for metal materials, which is composed of anionic water-dispersible resin and alkali metal silicate. In addition, Patent Document 4 proposes an organic resin coating formed by a surface treatment agent, which is composed of ammonium zirconium carbonate, a tetravalent vanadium compound, an organic phosphonic acid, and anionic water-dispersible acrylic resin.
[0006] The coating formed of inorganic materials and organic resins is disclosed in Japanese Patent Publication No. 2003-055777 (Patent Document 5) and Japanese Patent Publication No. 2005-097733 (Patent Document 6). Patent Document 5 proposes a surface-treated steel sheet having a coating formed of a zirconium compound and a vanadium compound on a Zn-Al-Mg-Si alloy plated material. In addition, Patent Document 6 proposes a surface-treated steel sheet having a coating formed of a vanadium compound, a phosphate compound, a metal component, and an acrylic resin on a Zn-Al alloy plated material, the acrylic resin being composed of a specific monomer component.
[0007] In the surface treated steel sheets having these coatings, the corrosion resistance can be improved. However, in these surface treated steel sheets, there are cases where sufficient adhesion with adhesives cannot be obtained. In addition, from the perspective of appearance, it is also required to suppress the blackening phenomenon in the surface treated steel sheets, that is, to improve the blackening resistance.
[0008] Therefore, a surface-treated steel plate that can obtain sufficient adhesion to an adhesive and sufficient blackening resistance together with corrosion resistance is proposed by International Publication No. 2017 / 155028 (Patent Document 7). The surface-treated steel plate disclosed in Patent Document 7 has a steel plate, a zinc-containing coating formed on the steel plate, and a coating formed on the coating. The coating contains acrylic resin, zirconium, vanadium, phosphorus and cobalt, and in the area from the surface to 1 / 5 of the thickness of the film thickness of the cross-section of the coating, the area ratio of the acrylic resin is 80 to 100 area%, and in the area consisting of an area with a thickness of 1 / 10 of the film thickness from the center of the film thickness to the surface side and an area with a thickness of 1 / 10 of the film thickness from the center of the film thickness to the coating side, the area ratio of the acrylic resin is 5 to 50 area%.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2002-030460
[0012] Patent Document 2: International Publication No. 2007 / 123276
[0013] Patent Document 3: International Publication No. 2007 / 069783
[0014] Patent Document 4: International Publication No. 2009 / 004684
[0015] Patent Document 5: Japanese Patent Application Publication No. 2003-055777
[0016] Patent Document 6: Japanese Patent Application Publication No. 2005-097733
[0017] Patent Document 7: International Publication No. 2017 / 155028 Summary of the invention
[0018] Problem that the invention aims to solve
[0019] In the surface-treated steel sheet disclosed in Patent Document 7, sufficient corrosion resistance, sufficient adhesion with an adhesive, and sufficient blackening resistance can be obtained.
[0020] However, in the case of condensation on the surface of the surface-treated steel plate, there is a case where the condensation portion changes color. In this specification, such a phenomenon is referred to as "condensation discoloration". Condensation discoloration does not have a particular effect on the mechanical properties of the surface-treated steel plate. However, lines are formed in the condensation portion, so the appearance of the surface-treated steel plate is reduced. Therefore, in the surface-treated steel plate, it is preferred to make condensation discoloration difficult to occur. In other words, the surface-treated steel plate is also required to have excellent condensation discoloration resistance.
[0021] An object of the present disclosure is to provide a surface-treated steel sheet that can obtain excellent corrosion resistance, excellent adhesion with an adhesive, and excellent blackening resistance, and can also obtain excellent condensation discoloration resistance.
[0022] Solutions for solving problems
[0023] The surface treated steel sheet disclosed in the present invention comprises:
[0024] Base steel plate;
[0025] a coating layer formed on a base steel plate; and
[0026] Chemical conversion film, which is formed on the coating,
[0027] The chemical composition of the coating contains in mass %
[0028] Al: more than 5.0% and less than 25.0%,
[0029] Mg: more than 3.0% and less than 12.5%,
[0030] Sn: 0-3.00%,
[0031] Bi: 0~5.00%,
[0032] In: 0~2.00%,
[0033] Ca: 0-3.00%,
[0034] Y: 0~3.00%,
[0035] La: 0-3.00%,
[0036] Ce: 0~3.00%,
[0037] Si: 0-2.50%,
[0038] Cr: 0~0.5%,
[0039] Ti: 0-0.5%,
[0040] Ni: 0-0.5%,
[0041] Co: 0-0.5%,
[0042] V: 0~0.5%,
[0043] Nb: 0-0.5%,
[0044] Cu: 0-0.5%,
[0045] Mn: 0~0.5%,
[0046] Fe: 0-5.0%,
[0047] Sr: 0~0.5%,
[0048] Sb: 0-0.5%,
[0049] Pb: 0-0.5%, and
[0050] B: 0~0.5%,
[0051] The balance is 65.0% or more of Zn and impurities,
[0052] Chemical conversion coating contains:
[0053] Zr, V, P and Co; and
[0054] Acrylic resin,
[0055] The adhesion amount of chemical conversion film is 300~1000mg / m 2 ,
[0056] V mass in chemical conversion film [V] mg / m 2 and P mass in chemical conversion film [P] mg / m 2 Satisfying formula (1),
[0057] The chemical composition of the coating is Mg content [Mg] b mass % and V mass [V] mg / m 2 Satisfying formula (2),
[0058] 0.60≤[V] / [P]≤2.80 (1)
[0059] 0<[V] / [Mg]b≤20.00 (2).
[0060] Effects of the Invention
[0061] In the surface-treated steel sheet of the present disclosure, excellent corrosion resistance, excellent adhesion with an adhesive, and excellent blackening resistance can be obtained, and further, excellent condensation discoloration resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1This is a graph of glow discharge emission spectra (GDS spectra) of elements in the chemical conversion film and the plating layer of the surface treated steel sheet.
[0063] Figure 2 This is a cross-sectional view perpendicular to the rolling direction of the surface-treated steel sheet according to the present embodiment.
[0064] Figure 3 This is a side view of a lap shear test piece used in an adhesion evaluation test in Examples. DETAILED DESCRIPTION
[0065] The present inventors conducted investigations and studies to solve the above problems. As a result, the present inventors obtained the following findings.
[0066] In a base steel plate formed with a coating containing Zn as a main component and also containing, by mass%, more than 5.0% and less than 25.0% of Al, and more than 3.0% and less than 12.5% of Mg, there is the possibility that excellent corrosion resistance can be obtained as long as the chemical conversion film formed on the coating contains Zr, V, P and Co, and an acrylic resin.
[0067] Therefore, the corrosion resistance, adhesion with adhesives, and blackening resistance of the surface-treated steel sheet having the above-mentioned technical features were investigated. As a result, the present inventors further obtained the following findings.
[0068] The adhesion between the adhesive and the adhesive depends on the amount of the chemical conversion film of the above composition. Specifically, if the amount of the chemical conversion film is 300 to 1000 mg / m 2 , excellent adhesion can be obtained in surface treated steel plates.
[0069] Furthermore, the mass of V in the chemical conversion film is defined as [V] (mg / m 2 ), the mass of P is defined as [P](mg / m 2 ). In this case, corrosion resistance and blackening resistance are affected by [V] / [P]. Specifically, if [V] / [P] is less than 0.60, sufficient blackening resistance cannot be obtained. The mechanism is not clear, but it is believed that if the P mass [P] is too much, the oxidation reaction of the plating material, which is the cause of blackening, is promoted. On the other hand, if [V] / [P] is greater than 2.80, sufficient corrosion resistance cannot be obtained. The reason is that if the P mass [P] in the chemical conversion film is relatively too small relative to the V mass [V], the corrosion inhibition effect of the passivation film formed by P becomes smaller. As long as [V] / [P] satisfies formula (1), excellent corrosion resistance and excellent blackening resistance can be obtained.
[0070] 0.60≤[V] / [P]≤2.80 (1)
[0071] However, even with the surface-treated steel sheet having the above-mentioned structure, there are still cases where sufficient condensation discoloration resistance cannot be obtained. Therefore, the present inventors have conducted further research. As a result, the present inventors have newly obtained the following findings.
[0072] The resistance to condensation discoloration is affected by the V mass [V] (mg / m 2 ) and the Mg content [Mg]b (mass %) of the coating in terms of mass %. Specifically, as long as the V mass [V] (mg / m 2 ) and the Mg content [Mg]b (mass %) in the plating layer satisfy formula (2), sufficient resistance to condensation discoloration can be obtained.
[0073] 0<[V] / [Mg]b≤20.00 (2)
[0074] This point will be described below.
[0075] The inventors of the present invention used an electron beam microanalyzer (EPMA) on the surface of the surface treated steel plate to measure the concentrations of the main elements in the area where condensation discoloration occurred and the area where condensation discoloration did not occur. As a result, in the area where condensation discoloration occurred, [V] / [Mg]b was greater than 20.00. On the other hand, in the area where condensation discoloration did not occur, [V] / [Mg]b was greater than 0 and was less than 20.00. Therefore, in the case where the above-mentioned chemical conversion film containing V is formed on the above-mentioned coating with a Mg content greater than 3.0%, if [V] / [Mg]b is less than 20.00, the occurrence of condensation discoloration can be suppressed, and sufficient condensation resistance can be obtained.
[0076] The surface-treated steel sheet of the present embodiment is completed based on the above technical ideas and has the following configuration.
[0077] The surface treated steel sheet of the first technical solution comprises:
[0078] Base steel plate;
[0079] a coating layer formed on a base steel plate; and
[0080] Chemical conversion film, which is formed on the coating,
[0081] The chemical composition of the coating contains in mass %
[0082] Al: more than 5.0% and less than 25.0%,
[0083] Mg: more than 3.0% and less than 12.5%,
[0084] Sn: 0-3.00%,
[0085] Bi: 0~5.00%,
[0086] In: 0~2.00%,
[0087] Ca: 0-3.00%,
[0088] Y: 0~3.00%,
[0089] La: 0-3.00%,
[0090] Ce: 0~3.00%,
[0091] Si: 0-2.50%,
[0092] Cr: 0~0.5%,
[0093] Ti: 0-0.5%,
[0094] Ni: 0-0.5%,
[0095] Co: 0-0.5%,
[0096] V: 0~0.5%,
[0097] Nb: 0-0.5%,
[0098] Cu: 0-0.5%,
[0099] Mn: 0~0.5%,
[0100] Fe: 0-5.0%,
[0101] Sr: 0~0.5%,
[0102] Sb: 0-0.5%,
[0103] Pb: 0-0.5%, and
[0104] B: 0~0.5%,
[0105] The balance is 65.0% or more of Zn and impurities,
[0106] Chemical conversion coating contains:
[0107] Zr, V, P and Co; and
[0108] Acrylic resin,
[0109] The adhesion amount of chemical conversion film is 300~1000mg / m 2 ,
[0110] V mass in chemical conversion film [V] mg / m 2 and P mass in chemical conversion film [P] mg / m2 Satisfying formula (1),
[0111] The chemical composition of the coating is Mg content [Mg] b mass % and V mass [V] mg / m 2 Satisfying formula (2),
[0112] 0.60≤[V] / [P]≤2.80 (1)
[0113] 0<[V] / [Mg]b≤20.00 (2).
[0114] A surface-treated steel sheet according to a second aspect of the present invention is a surface-treated steel sheet according to the first aspect of the present invention, wherein, further, the Mg concentration difference Δ[Mg] mass % which is the difference between the Mg concentration [Mg] s mass % at the surface layer of the coating layer and the Mg content [Mg] b mass % in the chemical composition of the coating layer obtained by elemental analysis in the depth direction of the coating layer using glow discharge emission spectrometry and the V mass [V] mg / m 2 Satisfying formula (3),
[0115] Δ[Mg]×[V]≤200 (3).
[0116] Figure 1 This is a graph of glow discharge emission spectra (GDS spectra) of elements in the chemical conversion film and the plating layer obtained by performing glow discharge emission spectrometry on the surface of the chemical conversion film of the surface-treated steel sheet along the sheet thickness direction. Figure 1 The horizontal axis represents the depth from the surface (measurement time), and the vertical axis represents the concentration (luminescence intensity) of each element.
[0117] exist Figure 1 In the graph, the luminescence intensity of carbon (C) is high from the surface of the surface-treated steel sheet (position 0 in the horizontal axis) to a predetermined depth. This means that the area with high luminescence intensity of C is the area of the chemical conversion film. On the other hand, the area with high luminescence intensity of Mg and Al is the area of the plating layer.
[0118] Reference Figure 1 In the surface treated steel sheet satisfying formula (1) and formula (2), the inventors of the present invention paid attention to the concentration of Mg in the surface area of the coating layer in contact with the chemical conversion film. In addition, the inventors of the present invention thought whether it is possible to further suppress condensation discoloration by utilizing the synergistic reaction between the Mg concentration in the surface layer of the coating layer and the components in the chemical conversion film in the surface treated steel sheet satisfying formula (1) and formula (2). Therefore, based on the above investigation, the inventors of the present invention conducted further research. As a result, the following matters were clarified.
[0119] In the surface treated steel sheet satisfying equations (1) and (2), Mg in the plating layer and V in the chemical conversion film affect condensation discoloration. Figure 1As shown, by reducing the Mg concentration difference Δ[Mg] which is the difference between the Mg concentration [Mg]s (mass %) at the surface layer of the coating and the Mg content [Mg]b (mass %) in the chemical composition of the coating, or by suppressing the V mass [V] in the chemical conversion film to a lower level, the synergistic effect between Mg and V can be utilized to further suppress condensation discoloration.
[0120] Based on the above findings, the present inventors further investigated the relationship between the Mg concentration difference Δ[Mg] of the plating layer, the V mass [V] in the chemical conversion film, and condensation discoloration. As a result, the present inventors also found the following findings.
[0121] As long as the Mg concentration difference Δ[Mg] (mass %) of the plated layer and the V mass [V] (mg / m 2 ) satisfies formula (3), and in the surface-treated steel sheet, excellent corrosion resistance, excellent adhesion with the adhesive, and excellent blackening resistance can be obtained, and furthermore, more excellent condensation discoloration resistance can be obtained.
[0122] Δ[Mg]×[V]≤200 (3)
[0123] The surface-treated steel sheet according to the third invention is the surface-treated steel sheet according to the first invention or the second invention, wherein the chemical composition of the coating layer contains, in mass %, a selected
[0124] Sn: 0.01~3.00%,
[0125] Bi: 0.01~5.00%,
[0126] In: 0.01~2.00%,
[0127] Ca: 0.01-3.00%,
[0128] Y: 0.01~3.00%,
[0129] La: 0.01~3.00%
[0130] Ce: 0.01~3.00%,
[0131] Si: 0.01-2.50%,
[0132] Cr: 0.1~0.5%,
[0133] Ti: 0.1-0.5%,
[0134] Ni: 0.1-0.5%,
[0135] Co: 0.1-0.5%,
[0136] V: 0.1~0.5%,
[0137] Nb: 0.1-0.5%,
[0138] Cu: 0.1-0.5%,
[0139] Mn: 0.1-0.5%,
[0140] Fe: 0.1-5.0%,
[0141] Sr: 0.1~0.5%,
[0142] Sb: 0.1-0.5%,
[0143] Pb: 0.1-0.5%, and
[0144] B: One or more elements selected from the group consisting of 0.1 to 0.5%.
[0145] Below, while referring to the attached Figure 1 The surface treated steel sheet of the present embodiment will be described. In the drawings, substantially the same structure is denoted by the same reference numerals and the description thereof is omitted. "%" indicating the content of each element means mass % unless otherwise specified.
[0146] [Structure of surface treated steel sheet]
[0147] Figure 2 2 is a cross-sectional view perpendicular to the rolling direction of the surface treated steel sheet of the present embodiment. Figure 2 The surface treated steel sheet 1 includes a base steel sheet 10, a coating 20, and a chemical conversion film 30. The coating 20 is formed on the surface of the base steel sheet 10. The chemical conversion film 30 is formed on the surface of the coating 20. The coating 20 may be formed on a single surface of the base steel sheet 10, or may be formed on both surfaces of the base steel sheet 10. In the case where the coating 20 is formed on both surfaces of the base steel sheet 10, the chemical conversion film 30 may be formed only on the coating 20 on a single surface, or may be formed on the coating 20 on both surfaces.
[0148] [For base steel plate 10]
[0149] The base steel plate 10 is not particularly limited. For example, it may be a steel plate whose microstructure is mainly composed of ferrite. It may also be a steel plate whose microstructure is mainly composed of ferrite and pearlite. It may also be a steel plate whose microstructure is mainly composed of one or more of ferrite, martensite and bainite. The type of the base steel plate 10 has no particular effect on the effect of the surface-treated steel plate 1 of the present embodiment. Therefore, the base steel plate 10 is not particularly limited.
[0150] [For plating layer 20]
[0151] The plating layer 20 is formed on the surface (one or both surfaces) of the base steel plate 10. The plating layer 20 contains, by mass%, Al: greater than 5.0% and less than 25.0%, Mg: greater than 3.0% and less than 12.5%, and Zn: 65.0% or more. Each element is described below.
[0152] Al: more than 5.0% and less than 25.0%
[0153] Aluminum (Al) is an easily oxidizable element and improves the corrosion resistance of the plating layer 20 by sacrificial corrosion protection. If the Al content is greater than 5.0% and less than 25.0%, the above effect can be fully obtained.
[0154] The lower limit of the Al content is preferably 5.1%, more preferably 7.5%, further preferably 10.0%, further preferably 12.0%.
[0155] The upper limit of the Al content is preferably 24.9%, more preferably 24.5%, more preferably 24.0%, more preferably 22.0%, and still more preferably 20.0%.
[0156] The preferred range of the Al content is, for example, 5.1 to 24.9%, more preferably 7.5 to 24.5%, more preferably 10.0 to 24.0%, more preferably 12.0 to 22.0%, and still more preferably 12.0 to 20.0%.
[0157] Mg: more than 3.0% and less than 12.5%
[0158] Magnesium (Mg) is an easily oxidizable element and improves the corrosion resistance of the plating layer 20 by sacrificial corrosion protection. If the Mg content is greater than 3.0% and less than 12.5%, the above effect can be fully obtained.
[0159] The lower limit of the Mg content is preferably 3.1%, more preferably 3.5%, more preferably 4.0%, more preferably 4.5%, more preferably 5.0%, and more preferably 5.5%.
[0160] The upper limit of the Mg content is preferably 12.4%, more preferably 12.0%, further preferably 11.0%, further preferably 10.0%.
[0161] The preferred range of the Mg content is, for example, 3.1 to 12.4%, more preferably 3.5 to 12.0%, more preferably 4.0 to 11.0%, more preferably 4.5 to 10.0%, more preferably 5.0 to 10.0%, and more preferably 5.5 to 10.0%.
[0162] The balance of the chemical composition of the plating layer 20 of the present embodiment is 65.0% or more of Zn and impurities.
[0163] As described above, the plating layer 20 mainly contains Zn. Specifically, the plating layer 20 contains 65.0% or more of Zn in terms of mass %. When the Zn content of the plating layer 20 is 65.0% or more in terms of mass %, sufficient corrosion resistance can be obtained.
[0164] The lower limit of the Zn content is preferably 67.5%, more preferably 70.0%.
[0165] The upper limit of the Zn content is preferably less than 92.0%, more preferably 90.0%, further preferably 85.0%, further preferably 80.0%.
[0166] The preferred range of the Zn content is, for example, 67.5% or more and less than 92.0%, more preferably 70.0 to 90.0%, further preferably 70.0 to 85.0%, and further preferably 70.0 to 80.0%.
[0167] The impurities mentioned above are elements mixed from the raw materials of the coating layer 20 or the manufacturing environment when the surface-treated steel sheet 1 is industrially manufactured, and are tolerable elements within a range that does not adversely affect the coating layer 20 of the present embodiment.
[0168] [For any element]
[0169] The chemical composition of the plating layer 20 may further contain one or more elements selected from the following Group 1 to Group 6 in place of a part of Zn.
[0170] [Group 1 (Sn Group)]
[0171] Sn: 0-3.00%,
[0172] Bi: 0 to 5.00%, and
[0173] In: 0~2.00%
[0174] [Group 2 (Ca group)]
[0175] Ca: 0-3.00%,
[0176] Y: 0~3.00%,
[0177] La: 0 to 3.00%, and
[0178] Ce: 0~3.00%
[0179] [Group 3]
[0180] Si: 0-2.50%
[0181] [Group 4 (Cr group)]
[0182] Cr: 0~0.5%,
[0183] Ti: 0-0.5%,
[0184] Ni: 0-0.5%,
[0185] Co: 0-0.5%,
[0186] V: 0~0.5%,
[0187] Nb: 0-0.5%,
[0188] Cu: 0-0.5%, and
[0189] Mn: 0~0.5%
[0190] [Group 5]
[0191] Fe: 0-5.0%
[0192] [Group 6 (Sr Group)]
[0193] Sr: 0~0.5%,
[0194] Sb: 0-0.5%,
[0195] Pb: 0-0.5%, and
[0196] B: 0~0.5%
[0197] Hereinafter, the first to sixth groups will be described.
[0198] [Group 1 (Sn, Bi and In)]
[0199] Alternatively, the chemical composition of the plating layer 20 may further contain one or more elements selected from the group consisting of tin (Sn), bismuth (Bi), and indium (In) to replace a portion of Zn. These elements are arbitrary elements and may not be contained. That is, the Sn content, Bi content, and In content may each be 0%.
[0200] When contained, these elements form intermetallic compounds with Mg. As a result, the corrosion resistance of the surface-treated steel sheet is improved. As long as at least one of Sn, Bi and In is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0201] However, if the content of these elements is too high, the viscosity of the plating solution increases even if the content of other elements is within the range of the present embodiment. In this case, the appearance quality of the surface-treated steel sheet 1 decreases.
[0202] Therefore, the Sn content is 0 to 3.00%, the Bi content is 0 to 5.00%, and the In content is 0 to 2.00%.
[0203] The preferred lower limit of the Sn content is greater than 0%, more preferably 0.01%, and further preferably 0.05%. The preferred upper limit of the Sn content is 2.70%, further preferably 2.50%, further preferably 2.00%, and further preferably 1.70%.
[0204] The preferred range of the Sn content is, for example, greater than 0 and 2.70% or less, more preferably 0.01 to 2.50%, further preferably 0.05 to 2.00%, and further preferably 0.05 to 1.70%.
[0205] The preferred lower limit of the Bi content is greater than 0%, more preferably 0.01%, and further preferably 0.05%. The preferred upper limit of the Bi content is 4.80%, further preferably 4.50%, and further preferably 4.00%.
[0206] The preferred range of the Bi content is, for example, greater than 0 and 4.80% or less, more preferably 0.01 to 4.50%, and even more preferably 0.05 to 4.00%.
[0207] The preferred lower limit of the In content is greater than 0%, more preferably 0.01%, and further preferably 0.05%. The preferred upper limit of the In content is 1.90%, further preferably 1.80%, and further preferably 1.70%.
[0208] The preferred range of the In content is, for example, greater than 0 and 1.90% or less, more preferably 0.01 to 1.80%, and further preferably 0.05 to 1.70%.
[0209] [Group 2 (Ca, Y, La and Ce)]
[0210] The chemical composition of the plating layer 20 may further contain one or more elements selected from the group consisting of calcium (Ca), yttrium (Y), lanthanum (La), and cerium (Ce) to replace a part of Zn. These elements are all arbitrary elements and may not be contained. That is, the content of these elements may also be 0%.
[0211] When contained, these elements form intermetallic compounds with Al and Zn in the coating layer 20. As a result, the corrosion resistance of the surface-treated steel sheet 1 is improved. As long as these elements are contained, even if the content is small, the above-mentioned effects can be obtained to a certain extent.
[0212] However, if the content of these elements is too high, even if the content of other elements is within the range of the present embodiment, the oxidation scum increases. In this case, the appearance quality of the surface-treated steel sheet 1 decreases.
[0213] Therefore, the Ca content is 0 to 3.00%, the Y content is 0 to 3.00%, the La content is 0 to 3.00%, and the Ce content is 0 to 3.00%.
[0214] The lower limit of the content of each element of Ca, Y, La and Ce is preferably more than 0%, more preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.
[0215] The upper limit of the content of each element of Ca, Y, La, and Ce is preferably 2.80%, more preferably 2.50%, and further preferably 2.00%.
[0216] The preferred range of the content of each element of Ca, Y, La and Ce is, for example, greater than 0 and 2.80% or less, more preferably 0.01 to 2.50%, further preferably 0.05 to 2.00%, and further preferably 0.10 to 2.00%.
[0217] [Group 3 (Si)]
[0218] The chemical composition of the plating layer 20 may further contain silicon (Si) in place of a portion of Zn. Si is an arbitrary element and may not be contained. That is, the Si content may be 0%.
[0219] When contained, Si improves the corrosion resistance of the surface-treated steel sheet 1. As long as Si is contained, even if the content is small, the above-mentioned effect can be obtained to a certain extent.
[0220] However, if the Si content is too high, the viscosity of the plating solution increases even if the contents of other elements are within the ranges of the present embodiment. In this case, the appearance quality of the surface-treated steel sheet 1 decreases.
[0221] Therefore, the Si content is 0 to 2.50%.
[0222] The lower limit of the Si content is preferably greater than 0%, more preferably 0.01%, further preferably 0.05%, further preferably 0.10%.
[0223] The upper limit of the Si content is preferably 2.00%, more preferably 1.50%, further preferably 1.00%, further preferably 0.50%.
[0224] The preferred range of the Si content is, for example, greater than 0 and 2.00% or less, more preferably 0.01 to 1.50%, further preferably 0.05 to 1.00%, and further preferably 0.10 to 0.50%.
[0225] [Group 4 (Cr, Ti, Ni, Co, V, Nb, Cu and Mn)]
[0226] Alternatively, the chemical composition of the plating layer 20 may further contain one or more elements selected from the group consisting of chromium (Cr), titanium (Ti), nickel (Ni), cobalt (Co), vanadium (V), niobium (Nb), copper (Cu), and manganese (Mn) to replace a portion of Zn. These elements are all arbitrary elements and may not be contained. That is, the content of these elements may also be 0%.
[0227] When contained, these elements improve the appearance quality of the surface-treated steel sheet 1. These elements also form intermetallic compounds with Al in the coating layer 20. As a result, the corrosion resistance of the surface-treated steel sheet 1 is improved. As long as these elements are contained, even if the content is small, the above-mentioned effects can be obtained to a certain extent.
[0228] However, if the content of these elements is too high, the viscosity of the plating solution increases even if the content of other elements is within the range of the present embodiment. In this case, the appearance quality of the surface-treated steel sheet 1 decreases.
[0229] Therefore, the Cr content is 0 to 0.5%, the Ti content is 0 to 0.5%, the Ni content is 0 to 0.5%, the Co content is 0 to 0.5%, the V content is 0 to 0.5%, the Nb content is 0 to 0.5%, the Cu content is 0 to 0.5%, and the Mn content is 0 to 0.5%.
[0230] The lower limit of the content of each element of Cr, Ti, Ni, Co, V, Nb, Cu and Mn is preferably greater than 0%, more preferably 0.1%.
[0231] The upper limit of the content of each element of Cr, Ti, Ni, Co, V, Nb, Cu, and Mn is preferably less than 0.5%, more preferably 0.4%.
[0232] The preferred range of the content of each element of Cr, Ti, Ni, Co, V, Nb, Cu, and Mn is, for example, greater than 0 and less than 0.5%, and more preferably 0.1 to 0.4%.
[0233] [Group 5 (Fe)]
[0234] The chemical composition of the plating layer 20 may further contain Fe in place of a part of Zn. That is, the Fe content may be 0%.
[0235] When contained, Fe increases the hardness of the coating layer 20 and improves the workability of the surface-treated steel sheet 1. As long as Fe is contained, even if the content is small, the above-mentioned effects can be obtained to a certain extent.
[0236] However, if the Fe content is too high, the hardness of the coating layer becomes too high even if the contents of other elements are within the ranges of the present embodiment. In this case, the workability of the surface-treated steel sheet 1 is reduced.
[0237] Therefore, the Fe content is 0 to 5.0%.
[0238] The lower limit of the Fe content is preferably greater than 0%, more preferably 0.1%, and further preferably 0.5%.
[0239] The upper limit of the Fe content is preferably 4.5%, more preferably 4.0%, and further preferably 3.5%.
[0240] The preferred range of the Fe content is, for example, greater than 0 and 4.5% or less, more preferably 0.1 to 4.0%, and even more preferably 0.5 to 3.5%.
[0241] [Group 6 (Sr, Sb, Pb and B)]
[0242] The chemical composition of the plating layer 20 may further contain one or more elements selected from the group consisting of strontium (Sr), antimony (Sb), lead (Pb) and boron (B) to replace a part of Zn. These elements are all arbitrary elements and may not be contained. That is, the content of these elements may also be 0%.
[0243] When contained, these elements enhance the metallic gloss of the plated layer 20 and improve the appearance quality of the surface-treated steel sheet 1. As long as these elements are contained, even if the contained amount is small, the above-mentioned effects can be obtained to a certain extent.
[0244] However, if the content of these elements is too high, even if the content of other elements is within the range of the present embodiment, the oxidation scum increases. In this case, the appearance quality of the surface-treated steel sheet 1 decreases.
[0245] Therefore, the Sr content is 0 to 0.5%, the Sb content is 0 to 0.5%, the Pb content is 0 to 0.5%, and the B content is 0 to 0.5%.
[0246] The lower limit of the content of each element of Sr, Sb, Pb and B is preferably more than 0%, and more preferably 0.1%.
[0247] The upper limit of the content of each element of Sr, Sb, Pb and B is preferably less than 0.5%, and more preferably 0.4%.
[0248] The content of each element of Sr, Sb, Pb and B is preferably in a range of, for example, greater than 0 and less than 0.5%, more preferably 0.1 to 0.4%.
[0249] [Preferred adhesion amount of the plating layer 20]
[0250] The adhesion amount of the plating layer 20 (mg / m 2 The preferred coating weight of the plating layer 20 is, for example, 20 to 500 mg / m 2 The lower limit of the coating weight of the plating layer 20 is preferably 30 mg / m 2 , more preferably 40 mg / m 2 , more preferably 50 mg / m 2 The upper limit of the coating weight of the plating layer 20 is preferably 400 mg / m 2 , more preferably 300 mg / m 2 , more preferably 200 mg / m 2 The preferred range of the coating weight of the plating layer 20 is, for example, 30 to 400 mg / m 2 , more preferably 40 to 300 mg / m 2 , more preferably 50 to 200 mg / m 2 .
[0251] [Method for measuring the chemical composition and adhesion amount of the plating layer 20]
[0252] The content (mass %) of each element in the chemical composition of the plating layer 20 and the adhesion amount (mg / m 2 ).
[0253] First, the thickness of the plating layer 20 and the thickness of the chemical conversion film 30 of the surface-treated steel sheet 1 are measured.
[0254] Specifically, a test piece including a cross section perpendicular to the surface of the surface-treated steel plate 1 is collected, and the cross section is used as the observation surface. The observation surface is mirror-polished. The region including the chemical conversion film 30, the plating layer 20, and at least the surface layer of the base steel plate 10 in the mirror-polished observation surface is observed with a scanning electron microscope (SEM). The magnification is set to 400 times.
[0255] In the observation field, the chemical conversion film 30 and the plating layer 20 can be clearly distinguished by contrast. The thickness (μm) of the plating layer 20 and the thickness (μm) of the chemical conversion film 30 are obtained at any five locations in the observation field. The arithmetic mean of the thicknesses of the plating layer 20 at the five locations is set as the thickness (μm) of the plating layer 20. Similarly, the arithmetic mean of the thicknesses of the chemical conversion film 30 at the five locations is set as the thickness (μm) of the chemical conversion film 30.
[0256] Next, a plurality of test pieces including the chemical conversion film 30, the coating 20, and the base steel plate 10 are collected from the surface treated steel plate 1. Hereinafter, these test pieces are referred to as basic test pieces. The thickness of the basic test piece is set to the thickness of the surface treated steel plate 1. In one basic test piece, the coating 20 and the chemical conversion film 30 are completely dissolved with hexamethylenetetramine hydrochloride. The elemental analysis based on ICP-MS (Inductively Coupled Plasma Mass Spectrometry) is performed on the dissolved liquid. Thus, the total adhesion amount (mg / m 2 ) and the mass of each element contained in the plating layer 20 and the chemical conversion film 30 (mg / m 2 ).
[0257] Next, another basic test piece is used to prepare a test piece for coating analysis. Specifically, the chemical conversion film 30 of the other basic test piece is removed by grinding. At this time, the thickness of the chemical conversion film 30 + (thickness of the coating 20 × 0.05) μm depth is removed from the surface of the basic test piece by grinding. The coating analysis test piece composed of the coating 20 and the base steel plate 10 is prepared by the above method.
[0258] In the test piece for plating analysis, the plating layer 20 was completely dissolved with hexamethylenetetramine hydrochloride. The dissolved solution was subjected to elemental analysis based on ICP-MS. Thus, the provisional adhesion amount (mg / m 2 ) and the tentative mass of each element contained in the coating 20 (mg / m 2 ).
[0259] The thickness of the coating 20 of the coating analysis test piece is 0.95 times the thickness of the coating 20 of the surface treated steel sheet 1. 2 The value of 1 / 0.95 times of ) is set as the adhesion amount of the plating layer 20 (mg / m 2 ).
[0260] In addition, the tentative mass (mg / m 2 ) is set as 1 / 0.95 times the mass of each element in the plating layer 20 (mg / m 2 ).
[0261] Based on the adhesion amount of the plating layer 20 (mg / m 2 ) and the mass of each element in the coating 20 (mg / m 2 ) The content (mass %) of each element in the plating layer 20 is calculated.
[0262] [For chemical conversion film 30]
[0263] The chemical conversion film 30 is formed on the surface of the plated layer 20. The chemical conversion film 30 contains Zr, V, P, and Co, and an acrylic resin.
[0264] [For Zr, V, P and Co]
[0265] Zirconium (Zr), vanadium (V), phosphorus (P) and cobalt (Co) all function as corrosion inhibitors of the surface-treated steel sheet 1, thereby improving the corrosion resistance of the surface-treated steel sheet 1. The corrosion environments in which Zr, V, P and Co effectively function as corrosion inhibitors are different. Therefore, Zr, V, P and Co are contained as corrosion inhibitors. As a result, in the surface-treated steel sheet 1, corrosion in various corrosive environments can be suppressed, and excellent corrosion resistance can be obtained.
[0266] [Regarding Zr in the Chemical Conversion Film 30]
[0267] The Zr in the chemical conversion film 30 forms a cross-linked structure with the acrylic resin. Therefore, the chemical conversion film 30 has excellent barrier properties. As a result, excellent corrosion resistance can be obtained in the surface-treated steel sheet 1. It is believed that Zr also forms a Zr-OM bond (M: metal element in the coating) with the surface of the coating 20. Therefore, Zr also improves the adhesion of the chemical conversion film 30 to the coating 20.
[0268] Preferably, the Zr mass [Zr] in the chemical conversion film 30 is 4.0 to 510.0 mg / m 2 If per unit area (1m 2 )’s Zr mass [Zr] is 4.0 mg / m 2 The above results in a further improvement in the adhesion between the Zr of the chemical conversion film 30 and the surface of the plating layer 20. In addition, due to the cross-linked structure formed by Zr and the acrylic resin in the chemical conversion film 30, the barrier property of the chemical conversion film 30 is further improved, and the corrosion resistance is further improved. If the Zr mass [Zr] is 510.0 mg / m 2 Below, the occurrence of cracks in the chemical conversion film 30 can be suppressed, and the corrosion resistance is further improved.
[0269] A further preferred lower limit of the Zr mass [Zr] is 50.0 mg / m 2 , more preferably 100.0 mg / m 2 , more preferably 120.0 mg / m 2 .
[0270] A further preferred upper limit of the Zr mass [Zr] is 500.0 mg / m 2, more preferably 400.0 mg / m 2 , more preferably 350.0 mg / m 2 .
[0271] The preferred range of the Zr mass [Zr] is, for example, 50.0 to 500.0 mg / m 2 , more preferably 100.0 to 400.0 mg / m 2 , more preferably 120.0 to 350.0 mg / m 2 .
[0272] [For V in the chemical conversion film 30]
[0273] V in the chemical conversion film 30 preferentially elutes toward the plating layer 20 under a corrosive environment. This suppresses a rise in pH due to dissolution of the plating layer 20. As a result, the corrosion resistance of the surface-treated steel sheet 1 is improved.
[0274] Preferably, the V mass [V] in the chemical conversion film 30 is 5.0 to 110.0 mg / m 2 If per unit area (1m 2 )'s V mass [V] is 5.0 mg / m 2 If the V mass [V] is 110.0 mg / m 2 After that, the condensation-induced discoloration resistance of the surface-treated steel sheet 1 is further improved.
[0275] The preferred lower limit of V mass [V] is 7.0 mg / m 2 , more preferably 10.0 mg / m 2 , more preferably 30.0 mg / m 2 , more preferably 50.0 mg / m 2 .
[0276] The preferred upper limit of V mass [V] is 100.0 mg / m 2 , more preferably 90.0 mg / m 2 , more preferably 80.0 mg / m 2 .
[0277] The preferred range of V mass [V] is, for example, 7.0 to 100.0 mg / m 2 , more preferably 10.0 to 90.0 mg / m 2 , more preferably 30.0 to 80.0 mg / m 2 , more preferably 50.0 to 80.0 mg / m 2 .
[0278] [For P in the chemical conversion film 30]
[0279] The P in the chemical conversion film 30 forms a passive film of zinc phosphate or the like on the surface of the plating layer 20. The corrosion resistance of the surface-treated steel sheet 1 is improved due to the passive film. The passive film is formed by the reaction of metal ions generated by the dissolution of a part of the plating layer 20 and P. The passive film is formed by applying an aqueous surface treatment agent containing P, which is a raw material of the chemical conversion film 30, to the surface of the plating layer 20, and / or dissolving a part of the plating layer 20 in a corrosive environment after the chemical conversion film 30 is formed.
[0280] Preferably, the P mass [P] in the chemical conversion film 30 is 20.0 to 200.0 mg / m 2 If per unit area (1m 2 ) is 20.0 mg / m 2 If the P mass [P] is 200.0 mg / m 2 After that, the blackening resistance of the surface-treated steel sheet 1 is further improved.
[0281] The preferred lower limit of P mass [P] is 20.0 mg / m 2 , more preferably 30.0 mg / m 2 , more preferably 40.0 mg / m 2 , more preferably 50.0 mg / m 2 .
[0282] The preferred upper limit of P mass [P] is 190.0 mg / m 2 , more preferably 180.0 mg / m 2 , more preferably 150.0 mg / m 2 , more preferably 100.0 mg / m 2 .
[0283] The preferred range of P mass [P] is, for example, 20.0 to 190.0 mg / m 2 , more preferably 30.0 to 180.0 mg / m 2 , more preferably 40.0 to 150.0 mg / m 2 , more preferably 50.0 to 100.0 mg / m 2 .
[0284] [For Co in the chemical conversion film 30]
[0285] The Co in the chemical conversion film 30 improves the blackening resistance and corrosion resistance of the surface-treated steel sheet 1. The Al and Mg in the coating 20 exhibit sacrificial corrosion protection in a corrosive environment. In this case, the Zn in the coating 20 oxidizes and changes color to black in an oxygen-deficient state. Such a phenomenon is called a blackening phenomenon. The blackening phenomenon tends to occur in the easily soluble portion of the coating 20. The Co in the chemical conversion film 30 delays the oxidation rate (corrosion rate) of the Zn in the coating 20. As a result, the blackening phenomenon can be suppressed, and the blackening resistance of the surface-treated steel sheet 1 is improved.
[0286] Preferably, the Co mass [Co] in the chemical conversion film 30 is 1.0 to 20.0 mg / m 2 If per unit area (1m 2 ) Co mass [Co] is 1.0 mg / m 2 If the Co mass [Co] is 20.0 mg / m 2 After that, the corrosion resistance of the surface-treated steel sheet 1 is further improved.
[0287] The preferred lower limit of Co mass [Co] is 2.0 mg / m 2 , more preferably 3.0 mg / m 2 , more preferably 4.0 mg / m 2 , more preferably 5.0 mg / m 2 .
[0288] The preferred upper limit of Co mass [Co] is 15.0 mg / m 2 , more preferably 12.0 mg / m 2 , more preferably 10.0 mg / m 2 , more preferably 8.0 mg / m 2 .
[0289] The preferred range of Co mass [Co] is, for example, 2.0 to 15.0 mg / m 2 , more preferably 3.0 to 12.0 mg / m 2 , more preferably 4.0 to 10.0 mg / m 2 , more preferably 5.0 to 8.0 mg / m 2 .
[0290] [Method for measuring the mass of Zr, V, P and Co in the chemical conversion film 30]
[0291] The amounts of Zr, V, P, and Co in the chemical conversion film 30 can be measured in the following manner.
[0292] The mass (mg / m2) of each element contained in the plating layer 20 and the chemical conversion film 30 was determined by the method described in the above-mentioned [Method for measuring the chemical composition and adhesion amount of the plating layer 20]. 2 ). Then, the mass (mg / m 2 ).
[0293] The mass (mg / m 2 ) minus the mass of each element in the coating 20 (mg / m 2 ) to find the Zr mass [Zr] (mg / m 2 )、V mass [V] (mg / m 2 )、P mass [P] (mg / m 2 ) and Co mass [Co] (mg / m 2 ).
[0294] [For acrylic resin]
[0295] The "acrylic resin" in this embodiment is a resin containing a polymer of (meth)acrylate. Preferably, the acrylic resin is a resin containing a polymer of alkyl (meth)acrylate. The acrylic resin may be a polymer obtained by polymerizing only alkyl (meth)acrylate, or a copolymer obtained by polymerizing alkyl (meth)acrylate and other monomers. In this specification, "(meth)acrylic acid" means "acrylic acid" or "methacrylic acid".
[0296] The acrylic resin improves the adhesion between the chemical conversion film 30 and the adhesive. The acrylic resin also improves the corrosion resistance of the surface-treated steel sheet 1.
[0297] When the acrylic resin is a copolymer of an alkyl (meth)acrylate and other monomers, the copolymer may be, for example, a copolymer of styrene (b1), (meth)acrylic acid (b2), an alkyl (meth)acrylate (b3), and acrylonitrile (b4).
[0298] Preferably, the acrylic resin is a copolymer containing 15 to 25% by mass of styrene (b1), 1 to 10% by mass of (meth)acrylic acid (b2), 40 to 58% by mass of (meth)acrylic acid alkyl ester (b3), and 20 to 38% by mass of acrylonitrile (b4). In the case where the acrylic resin is the above-mentioned copolymer, the adhesion with the adhesive is further improved. In addition, the corrosion resistance of the surface-treated steel plate 1 is further improved.
[0299] Styrene (b1) improves the adhesion between the chemical conversion film 30 and the adhesive. Styrene (b1) also improves the corrosion resistance of the surface-treated steel plate 1. If the styrene (b1) content is 15% by mass or more relative to the total mass of the monomer components (that is, when the acrylic resin is set to 100% by mass), the above-mentioned effect obtainable by using styrene (b1) is further improved. If the styrene (b1) content is 25% by mass or less, the excessive hardening of the chemical conversion film 30 can be suppressed. Therefore, the adhesion between the chemical conversion film 30 and the adhesive is further improved, and the corrosion resistance of the surface-treated steel plate 1 is further improved. Therefore, the preferred range of the styrene (b1) content is 15 to 25% by mass.
[0300] A more preferred lower limit of the styrene (b1) content is 17% by mass. A more preferred upper limit of the styrene (b1) content is 23% by mass. A more preferred range of the styrene (b1) content is, for example, 17 to 23% by mass.
[0301] (Meth) acrylic acid (b2) improves the adhesion between the chemical conversion film 30 and the plating layer 20 and the adhesive, and improves the corrosion resistance of the surface-treated steel sheet 1. If the content of (meth) acrylic acid (b2) is 1% by mass or more relative to the total mass of the monomer components (that is, when the acrylic resin is 100% by mass), the effect that can be obtained by (meth) acrylic acid (b2) is further improved. If the content of (meth) acrylic acid (b2) is 10% by mass or less, the water resistance of the chemical conversion film 30 is improved, and as a result, the corrosion resistance is further improved. Therefore, the preferred range of the content of (meth) acrylic acid (b2) is 1 to 10% by mass.
[0302] A more preferred lower limit of the content of (meth)acrylic acid (b2) is 2 mass %. A more preferred upper limit of the content of (meth)acrylic acid (b2) is 6 mass %. A more preferred range of the content of (meth)acrylic acid (b2) is, for example, 2 to 6 mass %.
[0303] The (meth) alkyl ester (b3) improves the corrosion resistance of the surface-treated steel plate 1. If the (meth) alkyl ester (b3) is 40% by mass or more relative to the total mass of the monomer components (that is, when the acrylic resin is set to 100% by mass), the corrosion resistance is further improved. In addition, if the content of the (meth) alkyl ester (b3) is 58% by mass or less, the corrosion resistance is further improved. Therefore, the preferred range of the (meth) alkyl ester (b3) is 40 to 58% by mass.
[0304] A more preferred lower limit of the content of the alkyl (meth)acrylate (b3) is 43% by mass. A more preferred upper limit of the content of the alkyl (meth)acrylate (b3) is 55% by mass. A more preferred range of the content of the alkyl (meth)acrylate (b3) is, for example, 43 to 55% by mass.
[0305] The (meth)acrylic acid alkyl ester (b3) is, for example, one or more substances selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-methylhexyl acrylate, and isomers thereof. Preferably, the (meth)acrylic acid alkyl ester (b3) is ethyl acrylate and / or butyl acrylate. In this case, the corrosion resistance is further improved.
[0306] Acrylonitrile (b4) improves the adhesion between the chemical conversion film 30 and the adhesive. If the content of acrylonitrile (b4) is 20% by mass or more relative to the total mass of the monomer components (that is, when the acrylic resin is 100% by mass), the adhesion between the chemical conversion film 30 and the adhesive is further improved. If the content of acrylonitrile (b4) is 38% by mass or less, the water resistance of the chemical conversion film 30 is improved, and the corrosion resistance is further improved. Therefore, the preferred range of acrylonitrile (b4) is 20 to 38% by mass.
[0307] A more preferred lower limit of the acrylonitrile (b4) content is 22% by mass. A more preferred upper limit of the acrylonitrile (b4) content is 35% by mass. A more preferred range of the acrylonitrile (b4) content is, for example, 22 to 35% by mass.
[0308] When the acrylic resin is a copolymer, it may be a copolymer containing styrene (b1), (meth)acrylic acid (b2), (meth)acrylic acid alkyl ester (b3), acrylonitrile (b4), and other vinyl-containing monomers.
[0309] Other vinyl-containing monomers are not particularly limited. Other vinyl-containing monomers are, for example, selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, 2-hydroxyethyl (meth)allyl ether, 3-hydroxypropyl (meth)allyl ether, 4-hydroxybutyl (meth)allyl ether, 2-dimethylaminoethyl acrylate, acrylamide, allyl alcohol, maleic acid, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, citraconic acid, cinnamic acid, vinyl trimethoxysilane, vinyl triethoxysilane, allyl glycidyl ether, glycidyl (meth)acrylate, 2-(1-aziridinyl)ethyl acrylate, imino methacrylate (iminol One or more substances selected from the group consisting of vinyl methacrylate, vinyl morpholine, vinyl formate, vinyl acetate, vinyl butyrate, vinyl acrylate, vinyl toluene, cinnamic acid nitrile, (meth)acryloyloxyethyl phosphate and bis-(meth)acryloyloxyethyl phosphate.
[0310] Preferably, the other vinyl-containing monomer is composed of one or more selected from the group consisting of 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, ethoxydiethylene glycol acrylate, and acrylamide. In this case, the stability of the emulsion is improved.
[0311] In the present specification, "(meth)acrylate" means "acrylate" or "methacrylate". "(meth)allyl ether" means "allyl ether" or "methallyl ether". "Methacryloyl" means "acryloyl" or "methacryloyl".
[0312] [Method for measuring the content of each component in the acrylic resin in the chemical conversion film 30]
[0313] The content (mass %) of each component of styrene (b1), (meth)acrylic acid (b2), (meth)acrylate alkyl ester (b3), and acrylonitrile (b4) in the acrylic resin is measured as follows by Fourier transform infrared spectroscopy using FT-IR reflection method, specifically, high sensitivity reflection method (RAS method).
[0314] A test piece (hereinafter referred to as a test piece for resin component analysis) containing a chemical conversion film 30 was collected from the surface-treated steel plate 1. The thickness of the test piece for resin component analysis was set to the thickness of the surface-treated steel plate 1. The 40 mm × 40 mm area in the test piece for resin component analysis was measured based on Fourier transform infrared spectroscopy under the condition of 16 cumulative times. At this time, the incident angle of infrared light to the chemical conversion film 30 was set to 70 to 75°. The horizontal axis was set to wave number (cm -1), a graph of an infrared absorption spectrum with the vertical axis being the transmittance (%).
[0315] In the infrared absorption spectrum chart, the heights of the main peaks of styrene (b1), (meth)acrylic acid (b2), alkyl (meth)acrylate (b3), and acrylonitrile (b4) were determined.
[0316] Next, calibration curves of styrene (b1), (meth)acrylic acid (b2), (meth)acrylic acid alkyl ester (b3), and acrylonitrile (b4) are prepared. For example, in the case of styrene (b1), a plurality of chemical conversion film samples having different contents (mass %) of styrene (b1) in the chemical conversion film 30 are prepared. The prepared chemical conversion film samples are subjected to Fourier transform infrared spectroscopy under the same conditions as those described above, and the height of the main peak of styrene (b1) is obtained. A calibration curve is prepared based on the obtained main peak height and the styrene (b1) content in the chemical conversion film sample. For (meth)acrylic acid (b2), (meth)acrylic acid alkyl ester (b3), and acrylonitrile (b4), calibration curves are also prepared using the same method as that for styrene (b1).
[0317] The contents (mass %) of styrene (b1), (meth)acrylic acid (b2), alkyl (meth)acrylate (b3), and acrylonitrile (b4) were determined based on the height of the main peak of each component obtained in the test piece for resin component analysis and the calibration curve of each component.
[0318] Preferably, the glass transition temperature of the acrylic resin is -12 to 24°C. If the glass transition temperature is -12°C or higher, the corrosion resistance of the chemical conversion film 30 is further improved. If the glass transition temperature is 24°C or lower, the adhesion with the adhesive is further improved. The preferred lower limit of the glass transition temperature of the acrylic resin is -10°C. The preferred upper limit of the glass transition temperature of the acrylic resin is 20°C.
[0319] The glass transition temperature of the acrylic resin was calculated using the following formula.
[0320] 1 / Tg(K)=W1 / Tg1+W2 / Tg2+···+W n / Tg n (1)
[0321] Wherein, Tg is the glass transition temperature (K) of the acrylic resin (A), W1, W2, ···, W n (n is a natural number) is the content (mass %) of the homopolymer of each monomer constituting the acrylic resin, Tg1, Tg2, .., Tg n (n is a natural number) is the glass transition temperature of the homopolymer of each monomer.
[0322] [Preferred Content of Acrylic Resin in Chemical Conversion Film 30]
[0323] The preferred content of acrylic resin in the chemical conversion film 30 as a whole is 20.0 to 60.0 mass %. If the content of acrylic resin is 20.0 mass % or more, the effect obtained by containing acrylic resin can be more effectively obtained. If the content of acrylic resin is 60.0 mass % or less, the corrosion resistance is further improved due to the synergistic effect brought about by containing Zr and acrylic resin.
[0324] The lower limit of the content of the acrylic resin is more preferably 25.0% by mass, and further preferably 30.0% by mass.
[0325] A more preferred upper limit of the content of the acrylic resin is 55.0% by mass, and further preferably 50.0% by mass.
[0326] A further preferred range of the content of the acrylic resin is, for example, 25.0 to 55.0% by mass, and further preferably 30.0 to 50.0% by mass.
[0327] [Method for Confirming and Measuring the Content of Acrylic Resin in Chemical Conversion Film 30]
[0328] The presence or absence of the acrylic resin contained in the chemical conversion film 30 and the content (mass %) of the acrylic resin can be confirmed by the following method.
[0329] A test piece including the chemical conversion film 30 , the plating layer 20 , and the base steel sheet 10 was collected from the surface-treated steel sheet 1 . The thickness of the test piece was set to the thickness of the surface-treated steel sheet 1 .
[0330] The test piece is subjected to thermal decomposition gas chromatography-mass spectrometry (GC-MS) analysis. Specifically, the test piece is heated to 600° C. using a GC-MS device. At this time, the resin in the chemical conversion film 30 is thermally decomposed to generate decomposition products. The decomposition products are analyzed by GC-MS to determine the type and amount of the decomposition products. The presence or absence of acrylic resin in the chemical conversion film 30 can be confirmed from the type of the decomposition products.
[0331] The content (mass %) of the acrylic resin in the chemical conversion film can be determined based on the amount of the analyzed decomposition product and the mass of the chemical conversion film 30. The total adhesion amount (mg / m2) of the plating layer 20 and the chemical conversion film 30 obtained by the method described in [Method for measuring the chemical composition and adhesion amount of the plating layer 20] can be obtained. 2 ), and the adhesion amount of the plating layer 20 (mg / m 2 ) Calculate the mass of the chemical conversion film 30.
[0332] [About the Adhesion Amount of the Chemical Conversion Film 30]
[0333] The adhesion amount of the chemical conversion film 30 is 300 to 1000 mg / m 2 If the adhesion amount of the chemical conversion film 30 is less than 300 mg / m 2 , the formed chemical conversion film 30 is too thin. In this case, the adhesion is reduced and the corrosion resistance is also reduced. On the other hand, if the adhesion amount of the chemical conversion film 30 is greater than 1000 mg / m 2 , the formed chemical conversion film 30 is too thick. In this case, the adhesiveness is reduced.
[0334] If the adhesion amount of the chemical conversion film 30 is 300 to 1000 mg / m 2 , the thickness of the chemical conversion film 30 is appropriate. Therefore, sufficient adhesion can be obtained, and sufficient corrosion resistance can be obtained.
[0335] The lower limit of the amount of the chemical conversion film 30 is preferably 350 mg / m 2 , more preferably 400 mg / m 2 , further preferably 450 mg / m 2 .
[0336] The upper limit of the amount of the chemical conversion film 30 is preferably 950 mg / m 2 , further preferably 900 mg / m 2 , more preferably 850 mg / m 2 .
[0337] The preferred range of the adhesion amount of the chemical conversion film 30 is 350 to 950 mg / m 2 , more preferably 400 to 900 mg / m 2 , more preferably 450 to 850 mg / m 2 .
[0338] [Method for measuring the adhesion amount of the chemical conversion film 30]
[0339] The adhesion amount of the chemical conversion film 30 can be obtained as follows.
[0340] The total adhesion amount (mg / m 2 ). Then, the adhesion amount (mg / m 2 ).
[0341] The total adhesion amount (mg / m 2 ) minus the amount of adhesion in the coating 20 (mg / m 2 ) and the adhesion amount of the chemical conversion film 30 (mg / m2 ).
[0342] [For formula (1)]
[0343] In the surface-treated steel sheet 1 of the present embodiment, the V mass [V] in the chemical conversion film 30 is mg / m 2 and P mass in the chemical conversion film 30 [P] mg / m 2 Satisfies formula (1).
[0344] 0.60≤[V] / [P]≤2.80 (1)
[0345] F1 is defined as follows.
[0346] F1=[V] / [P]
[0347] If F1 is less than 0.60, the P mass [P] in the chemical conversion film 30 is too much relative to the V mass [V]. In this case, the blackening resistance of the surface-treated steel plate 1 is reduced. If the P mass [P] is too much relative to the V mass [V], it is believed that the oxidation reaction of the plating material, which is the cause of blackening, will be promoted. On the other hand, if F1 is greater than 2.80, sufficient corrosion resistance cannot be obtained. The reason is that if the P mass [P] is too little relative to the V mass [V], the corrosion inhibition effect of the passivation film formed by P is reduced. If F1 is 0.60-2.80, excellent blackening resistance and excellent corrosion resistance can be obtained.
[0348] The lower limit of F1 is preferably 0.65, more preferably 0.70, and further preferably 0.80.
[0349] The upper limit of F1 is preferably 2.40, more preferably 2.00, and further preferably 1.80.
[0350] The preferred range of F1 is, for example, 0.65 to 2.40, more preferably 0.70 to 2.00, and even more preferably 0.80 to 1.80.
[0351] In addition, the V mass [V] (mg / m 2 ) and P mass [P] (mg / m 2 ) can be determined by the method described in the above-mentioned [Method for measuring the mass of Zr, mass of V, mass of P and mass of Co in the chemical conversion film 30].
[0352] [For formula (2)]
[0353] In the surface treated steel sheet 1 of the present embodiment, when the Mg content of the chemical composition of the coating layer 20 is further defined as [Mg]b (mass %), the Mg content [Mg]b (mass %) and the V mass [V] (mg / m2 ) satisfies formula (2).
[0354] 0<[V] / [Mg]b≤20.00 (2)
[0355] F2 is defined as follows.
[0356] F2=[V] / [Mg]b
[0357] When the Mg content of the chemical composition of the coating 20 is greater than 3.0 mass %, if the V mass [V] in the chemical conversion film 30 is high relative to the Mg content [Mg]b in the coating 20, condensation discoloration occurs. Specifically, if F2 is greater than 20.00, the V mass in the chemical conversion film 30 is too high relative to the Mg mass in the coating 20. In this case, sufficient condensation discoloration resistance cannot be obtained. If F2 is greater than 0 and is 20.00 or less, excellent condensation discoloration resistance can be obtained in the surface-treated steel sheet 1.
[0358] The preferred lower limit of F2 is 5.00, more preferably 6.00, further preferably 7.00.
[0359] The upper limit of F2 is preferably 19.00, more preferably 18.00, and further preferably 17.00.
[0360] The preferred range of F2 is, for example, 5.00 to 19.00, more preferably 6.00 to 18.00, and even more preferably 7.00 to 17.00.
[0361] [Effects of Surface-treated Steel Sheet 1]
[0362] In the surface-treated steel sheet 1 of the present embodiment, the plating layer 20 and the chemical conversion film 30 have the above-mentioned chemical composition, and the adhesion amount of the chemical conversion film 30 is 300 to 1000 mg / m 2 , and satisfying equations (1) and (2). Therefore, in the surface-treated steel plate 1 of the present embodiment, sufficient corrosion resistance, sufficient adhesion with the adhesive, and sufficient blackening resistance can be obtained, and sufficient condensation discoloration resistance can be obtained.
[0363] [Preferred Forms of Surface-treated Steel Sheet 1]
[0364] In the surface-treated steel sheet 1 of the present embodiment, the difference between the Mg concentration [Mg]s mass % at the surface layer of the coating 20 obtained by elemental analysis in the depth direction of the coating 20 using glow discharge emission spectrometry and the Mg content [Mg]b mass % in the chemical composition of the coating 20 is defined as the Mg concentration difference Δ[Mg] (mass %).
[0365] Preferably, in the surface-treated steel sheet 1 of the present embodiment, the Mg concentration difference Δ[Mg] (mass %) and the V mass [V] (mg / m 2 ) also satisfies formula (3).
[0366] Δ[Mg]×[V]≤200 (3)
[0367] F3 is defined as follows.
[0368] F3=Δ[Mg]×[V]
[0369] The Mg concentration difference Δ[Mg] of the plating layer 20 and the V mass [V] in the chemical conversion film 30 synergistically affect the condensation discoloration resistance. If the Mg concentration difference Δ[Mg] is low and the V mass [V] is small, the condensation discoloration resistance is further improved due to the synergistic effect between the concentrated Mg in the surface layer of the plating layer 20 and the V concentration in the chemical conversion film 30. Therefore, F3 is an indicator of condensation discoloration resistance.
[0370] When F3 is 200 or less, the interaction between the concentrated Mg in the surface layer of the plating layer 20 and the V in the chemical conversion film 30 can be sufficiently suppressed. As a result, the condensation discoloration resistance is significantly improved.
[0371] The upper limit of F3 is more preferably 180, more preferably 160, more preferably 150, more preferably 140, more preferably 130, and even more preferably 120.
[0372] The lower limit of F3 is not particularly limited. A preferred lower limit of F3 is, for example, 5, more preferably 10, more preferably 20, more preferably 25, and more preferably 30.
[0373] A further preferred range of F3 is, for example, 5 to 180, more preferably 10 to 160, more preferably 20 to 150, more preferably 25 to 140, more preferably 30 to 130, and even more preferably 30 to 120.
[0374] [Method for measuring Mg concentration difference Δ[Mg]]
[0375] The Mg concentration difference Δ[Mg] in the surface layer of the plating layer 20 can be obtained as follows.
[0376] A test piece is collected from the surface treated steel plate 1. The test piece includes a base steel plate 10, a coating 20 and a chemical conversion film 30. The thickness of the test piece is set to the thickness of the surface treated steel plate. Glow discharge emission spectrometry is performed from the surface of the chemical conversion film 30 of the test piece along the thickness direction of the base steel plate 10 to measure the glow discharge emission spectrum (GDS spectrum) of Mg and C. Specifically, a high-frequency glow discharge light emission device (GD-OES, trade name: GDA750 manufactured by Rigaku Corporation) is used, and in an argon atmosphere (Ar pressure: 3 hPa), the test piece is set as the cathode, and an electric power of 30 W is applied to measure the GDS spectrum of Mg and the GDS spectrum of C. The measurement area is set to , set the measurement time to 100 seconds and the measurement interval to 0.025 seconds.
[0377] Reference Figure 1 , the position P0 where the obtained GDS spectrum of Mg intersects with the GDS spectrum of C is set as the surface of the coating 20 (that is, the interface between the chemical conversion film 30 and the coating 20). The area SF within 10 seconds from the surface of the coating 20 is defined as the surface area SF of the coating 20. The maximum value of the Mg concentration in the surface area SF of the coating 20 is set as the Mg concentration [Mg]s (mass %). In addition, the Mg content in the chemical composition of the coating 20 obtained in [Method for measuring the chemical composition and adhesion amount of the coating 20] is set as [Mg]b (mass %).
[0378] The obtained Mg concentration [Mg]s and Mg content [Mg]b were used to determine the Mg concentration difference Δ[Mg] (mass %) by the following formula.
[0379] Δ[Mg]=[Mg]s-[Mg]b
[0380] [Regarding the Adhesive Applied to the Surface-treated Steel Plate 1]
[0381] Adhesives that can achieve good adhesion with the chemical conversion film 30 of the surface-treated steel plate 1 include, for example, silicone-based (including acrylic-modified and epoxy-modified), epoxy-based, acrylic resin-based, phenolic, urethane-based, vinyl acetate-based, cyanoacrylate-based, and styrene-butadiene rubber-based adhesives.
[0382] The material bonded to the chemical conversion film 30 of the surface-treated steel plate 1 by an adhesive is not particularly limited, and examples of the material include steel plate, mortar, float glass, ceramic tile, porcelain tile, and MDF (medium-density fiber board).
[0383] [Method for producing surface-treated steel sheet 1]
[0384] An example of a method for manufacturing a surface-treated steel plate according to the present embodiment is described. The surface-treated steel plate having the above-mentioned technical features can also be manufactured using other manufacturing methods other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing a surface-treated steel plate according to the present embodiment.
[0385] An example of a method for producing a surface-treated steel sheet according to the present embodiment includes the following steps.
[0386] (Process 1) Base steel plate preparation process
[0387] (Step 2) Plating layer forming step
[0388] (Process 3) Surface temper rolling process
[0389] (Step 4) Chemical Conversion Film Formation Step
[0390] Hereinafter, step 1 to step 4 will be described.
[0391] [(Process 1) Base material steel plate preparation process]
[0392] In the base steel plate preparing step, the above-mentioned base steel plate 10 is prepared. The base steel plate 10 may be supplied by a third party.
[0393] [(Step 2) Plating layer forming step]
[0394] In the coating forming process, a coating treatment (molten coating treatment) is applied to the base steel plate 10 to form a coating 20 on the surface of the base steel plate 10. Specifically, a coating solution is prepared. The composition of the coating solution is adjusted according to the composition of the coating 20 to be formed. After the base steel plate 10 is immersed in the coating solution for a certain period of time, the base steel plate 10 is pulled out of the coating solution by a well-known method. For example, a sinking roller is arranged in the coating solution. The traveling direction of the base steel plate 10 immersed in the coating solution is changed to the upper side by the sinking roller.
[0395] The plating material is attached to the surface of the base steel plate 10 pulled up from the plating solution. The amount of the plating material attached to the base steel plate 10 is adjusted by a well-known gas purge device. The plating material attached to the base steel plate 10 pulled up from the plating solution is cooled. The plating material is solidified by cooling to form a plating layer 20.
[0396] [Preferred Cooling Conditions in the Plating Layer Forming Step]
[0397] In the plating layer forming step, it is preferable that the following manufacturing condition 1 is satisfied.
[0398] (Preferred manufacturing condition 1)
[0399] The average cooling rate CR1 of the surface temperature of the base steel plate 10 with the plated material pulled up from the plating solution from 450°C to 340°C is set to 16-46°C / sec, and the average cooling rate CR2 from 340°C to 250°C is set to 21-51°C / sec.
[0400] If the average cooling rate CR1 is 16°C / sec or more and the average cooling rate CR2 is 21°C / sec or more, the structure of the solidified plating layer 20 becomes fine. Therefore, the concentration of Mg in the surface layer of the plating layer 20 can be sufficiently suppressed, and the Mg concentration difference Δ[Mg] can be sufficiently low. As a result, F3 satisfies the formula (3).
[0401] The upper limits of the average cooling rate CR1 and the average cooling rate CR2 are not particularly limited. The preferred upper limit of the average cooling rate CR1 is 46° C. / sec. The preferred upper limit of the average cooling rate CR2 is 51° C. / sec.
[0402] [(Process 3) Surface temper rolling process]
[0403] In the temper rolling step, the steel sheet after the plating layer forming step is subjected to temper rolling. In the temper rolling, the steel sheet on which the plating layer 20 is formed is cold rolled using a rolling mill having a pair of temper rolling rolls.
[0404] [Preferred manufacturing conditions in the temper rolling process]
[0405] In the temper rolling step, it is preferable that the following manufacturing conditions 2 and 3 are satisfied.
[0406] (Preferred manufacturing condition 2)
[0407] The arithmetic mean roughness Ra of the surface of the temper rolling roll in the roll axis direction was set to 1.0 to 5.0 μm, and the reduction force P (t) during temper rolling was set to 100 to 500 t.
[0408] (Preferred manufacturing condition 3)
[0409] The average cooling rates CR1 and CR2 (° C. / sec), the arithmetic mean roughness Ra (μm) of the surface of the temper rolling roll, and the reduction force P (t) during temper rolling satisfy the formula (A).
[0410] (CR1+CR2) / {2(Ra×P)}≥0.020(A)
[0411] Next, manufacturing condition 2 and manufacturing condition 3 are described.
[0412] [For preferred manufacturing conditions 2]
[0413] The surface roughness of the surface smooth rolling roller affects the Mg concentration of the surface layer of the coating 20. If the arithmetic mean roughness Ra is 5.0 μm or less, the value of the surface roughness of the coating 20 can be sufficiently suppressed. In this case, excessive concentration of Mg at the surface layer of the coating 20 can be suppressed, and the Mg concentration difference Δ[Mg] is sufficiently low. As a result, F3 satisfies formula (3). Therefore, it is preferred that the arithmetic mean roughness Ra of the surface of the surface smooth rolling roller is 5.0 μm or less.
[0414] The arithmetic mean roughness Ra is measured in the following manner.
[0415] In each pair of surface polishing rolls, the arithmetic mean roughness Ra of the surface in the roller axis direction is measured according to JIS B 0601:2013. A contact type roughness meter is used for the measurement of the arithmetic mean roughness Ra. The conditions for calculating the roughness curve are set as cutoff value λc: 80 mm, cutoff value λs: 80 μm, measurement speed: 0.5 mm / sec, reference length: 1 mm, and evaluation length: 10 mm. The arithmetic mean of the arithmetic mean roughness (a total of 2) obtained in each surface polishing roll is defined as the arithmetic mean roughness Ra (μm).
[0416] From the perspective of the Mg concentration difference Δ[Mg], the lower limit of the arithmetic mean roughness Ra is not particularly limited. However, if the arithmetic mean roughness Ra is too small, the base steel sheet 10 having the coating layer 20 formed thereon will have difficulty in biting into the surface tempering roll. Therefore, the lower limit of the arithmetic mean roughness Ra is 1.0 μm.
[0417] The reduction force P during skin-pass rolling affects the Mg concentration in the surface layer of the coating 20. If the reduction force P is 100 to 500 tons, the Mg concentration in the surface layer of the coating 20 can be sufficiently suppressed, and the Mg concentration difference Δ[Mg] is sufficiently low. As a result, F3 satisfies the formula (3). Therefore, it is preferred that the reduction force P is 100 to 500 tons.
[0418] [For preferred manufacturing conditions 3]
[0419] FA is defined as follows.
[0420] FA=(CR1+CR2) / {2(Ra×P)}
[0421] FA is an index related to the Mg concentration of the surface layer of the coating layer 20. As described above, the average cooling rates CR1 and CR2, the arithmetic mean roughness Ra, and the pressing force P affect the Mg concentration difference Δ[Mg]. If FA is 0.020 or more, the Mg concentration difference Δ[Mg] of the surface layer of the coating layer 20 of the surface-treated steel sheet 1 after manufacturing is sufficiently low on the premise of satisfying manufacturing conditions 1 and manufacturing conditions 2. As a result, F3 satisfies formula (3).
[0422] [(Step 4) Chemical Conversion Film Formation Step]
[0423] In the chemical conversion film forming step, an aqueous surface treatment agent containing components included in the chemical conversion film 30 is prepared, and the prepared aqueous surface treatment agent is applied onto the plated layer 20. The applied aqueous surface treatment agent is dried to form the chemical conversion film 30 on the plated layer 20.
[0424] [For water-based surface treatment agents]
[0425] The aqueous surface treatment agent contains Zr, V, P, Co, and acrylic resin. The aqueous surface treatment agent contains, for example, acrylic resin (A), zirconium carbonate compound (B), vanadium compound (C), phosphorus compound (D), cobalt compound (E), and water, and the pH of the aqueous surface treatment agent is 8.0 to 11.0.
[0426] [For acrylic resin (A)]
[0427] The acrylic resin (A) is coated with a water-based surface treatment agent and dried to become an acrylic resin contained in the chemical conversion film 30. The preferred content of the acrylic resin (A) in the water-based surface treatment agent is 20.0 to 60.0% by mass relative to the total solid content of the water-based surface treatment agent. Here, "relative to the total solid content" refers to the mass % of the water-based surface treatment agent when the components other than water are set to 100.0% by mass %. A further preferred lower limit of the content of the acrylic resin (A) in the water-based surface treatment agent is 25.0%. A further preferred upper limit of the content of the acrylic resin (A) in the water-based surface treatment agent is 40.0%. A further preferred range of the content of the acrylic resin (A) in the water-based surface treatment agent is 25.0 to 40.0%.
[0428] The polymerization method of the acrylic resin (A) contained in the water-based surface treatment agent is not particularly limited. For example, the acrylic resin (A) can be polymerized using suspension polymerization, emulsion polymerization, and solution polymerization. When polymerizing the acrylic resin (A), a solvent and / or a polymerization initiator can also be used. The polymerization initiator is not particularly limited. The polymerization initiator is, for example, a free radical polymerization initiator such as an azo compound, a peroxide compound, etc. It is preferred to use a polymerization initiator of 0.1 to 10% by mass relative to the total solid content of the acrylic resin. The reaction temperature and reaction time are well-known conditions. The reaction temperature is, for example, room temperature to 200°C, and the reaction time is 30 minutes to 8 hours.
[0429] [Zirconium carbonate compound (B)]
[0430] The zirconium carbonate compound (B) in the water-based surface treatment agent undergoes a cross-linking reaction with the acrylic resin (A) by applying the water-based surface treatment agent and drying it. As a result, a chemical conversion film 30 having a cross-linking structure between Zr and the acrylic resin (A) is formed. In addition, in the zirconium carbonate compound (B), carbonate ions volatilize when the water-based surface treatment agent is applied and dried. Moreover, the remaining Zr is bonded to each other with the help of oxygen to form a high molecular weight. As a result, the -Zr-OH group forms a Zr-OM bond (M: metal element in the coating) with the surface of the coating 20.
[0431] The type of zirconium carbonate compound (B) is not particularly limited. The zirconium carbonate compound (B) is, for example, one or more substances selected from the group consisting of zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, and sodium zirconium carbonate. Preferably, the zirconium carbonate compound (B) is zirconium carbonate and / or ammonium zirconium carbonate. In this case, the corrosion resistance is further improved.
[0432] [Vanadium compound (C)]
[0433] The vanadium compound (C) contained in the water-based surface treatment agent is, for example, a compound selected from a vanadium compound having a valence of 2 to 4, such as vanadium pentoxide (V2O5), metavanadic acid (HVO3), ammonium metavanadate, sodium metavanadate, vanadium trichloride (VOCl3), etc., which is reduced to a valence of 2 to 4 by a reducing agent, vanadium trioxide (V2O3), vanadium dioxide (VO2), vanadium sulfate (VOSO4), vanadium oxalate [VO(COO)2], vanadium acetylacetonate [VO(OC(CH3)=CHCOCH3)2], vanadium acetylacetonate [V(OC(CH3)=CHCOCH3)3], vanadium trichloride (VCl3), vanadium phosphomolybdate {H 15-X [PV 12-x Mo x O 40 One or more substances selected from the group consisting of vanadium compounds having an oxidation number of 4 to 2, such as vanadium sulfate (VSO4·8H2O), vanadium dichloride (VCl2), and vanadium oxide (VO).
[0434] [Phosphorus compound (D)]
[0435] The phosphorus compound (D) contained in the water-based surface treatment agent is, for example, an inorganic acid anion having an acid group containing phosphorus and / or an organic acid anion having an acid group containing phosphorus.
[0436] The inorganic acid anion having a phosphorus-containing acid radical is, for example, one or more substances selected from the group consisting of inorganic acid anions in which at least one hydrogen of an inorganic acid such as orthophosphoric acid, metaphosphoric acid, condensed phosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, tetraphosphoric acid, and hexametaphosphoric acid is freed, and their salts.
[0437] The organic acid anion having a phosphorus-containing acid radical is, for example, one or more substances selected from the group consisting of organic acid anions in which at least one hydrogen is freed, such as 1-hydroxymethane-1,1-diphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, 1-hydroxypropane-1,1-diphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, 2-hydroxyphosphonoacetic acid, aminotri(methylenephosphonic acid), ethylenediamine-N,N,N',N'-tetra(methylenephosphonic acid), hexamethylenediamine-N,N,N',N'-tetra(methylenephosphonic acid), diethylenetriamine-N,N,N',N",N"-penta(methylenephosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, inositol hexaphosphonic acid, phytic acid and other organic phosphonic acids, and organic phosphoric acids, and their salts.
[0438] [Cobalt compounds (E)]
[0439] The cobalt compound (E) contained in the water-based surface treatment agent is, for example, one or more substances selected from the group consisting of cobalt sulfate, cobalt nitrate, and cobalt carbonate.
[0440] [Lubricant]
[0441] The water-based surface treatment agent may also contain a lubricant. That is, the lubricant is an arbitrary component. When contained, the lubricant improves the scratch resistance of the surface-treated steel plate 1. The lubricant is, for example, one or more substances selected from the group consisting of polyethylene wax, oxidized polyethylene wax, and oxidized polypropylene wax.
[0442] [pH of water-based surface treatment agents]
[0443] Preferably, the pH of the aqueous surface treatment agent is 8.0 to 11.0. If the pH of the aqueous surface treatment agent is 8.0 or more, the zirconium carbonate compound (B) is stably dissolved in the aqueous surface treatment agent. On the other hand, if the pH of the aqueous surface treatment agent is 11.0 or less, it is possible to suppress excessive dissolution of the coating 20 when the aqueous surface treatment agent is applied to the coating 20. In addition, if the pH is within the above range, the aqueous surface treatment agent is stable. A further preferred lower limit of the pH of the aqueous surface treatment agent is 8.5. A further preferred upper limit of the pH of the aqueous surface treatment agent is 10.0. A further preferred range of the pH of the aqueous surface treatment agent is 8.0 to 11.0. For example, the pH of the aqueous surface treatment agent can be measured at a measurement temperature of 25°C using a DKK Toa Co., Ltd. (HM-30R).
[0444] The adjusting agent used for adjusting the pH of the aqueous surface treatment agent is not particularly limited and is, for example, one or more substances selected from the group consisting of ammonia, guanidine carbonate, carbonic acid, acetic acid, and hydrofluoric acid.
[0445] The water-based surface treatment agent can be obtained by mixing the above-mentioned components with water such as deionized water and distilled water.
[0446] It is also possible to add alcohol, ketone, glycol ether-based water-soluble solvents, surfactants, defoamers, leveling agents, antibacterial and antifungal agents, thickeners, conductive materials for improving weldability, coloring pigments for improving appearance design, matte materials, etc. to the water-based surface treatment agent as needed. Preferably, the addition amount of these components is less than 5% by mass relative to the total solid content of the water-based surface treatment agent.
[0447] The above-mentioned water-based surface treatment agent is applied to the surface of the coating layer 20 by a well-known method to form a coating film. For example, the water-based surface treatment agent is applied using a roll coater. In this case, the film thickness of the coating film can be adjusted by adjusting the peripheral speed ratio of the roll coater. The film thickness of the coating film is adjusted so that the adhesion amount of the chemical conversion film 30 becomes 300 to 1000 mg / m 2 After the coating film is formed on the surface of the plated layer 20 , the coating film is dried.
[0448] The surface-treated steel sheet 1 of the present embodiment is manufactured through the above-mentioned steps.
[0449] Example
[0450] The effects of the surface treated steel sheet of the present embodiment will be further specifically described using examples. The conditions in the following examples are an example of conditions used to confirm the feasibility and effects of the surface treated steel sheet of the present embodiment. Therefore, the surface treated steel sheet of the present embodiment is not limited to this example of conditions.
[0451] Base steel sheets on which plating layers having the chemical compositions listed in Table 1 (Table 1-1 and Table 1-2) were formed were prepared.
[0452] [Table 1-1]
[0453] Table 1-1
[0454]
[0455] [Table 1-2]
[0456] Table 1-2
[0457]
[0458] The coating is formed by hot-dip plating. The coating weight is 40 to 300 mg / m 2 within the range.
[0459] In addition, in the hot-dip coating treatment, the average cooling rate CR1 (°C / sec) when the surface temperature of the steel sheet pulled up from the coating solution is 450-340°C and the average cooling rate CR2 (°C / sec) when the surface temperature is 340-250°C is as shown in Table 2.
[0460] [Table 2]
[0461] Table 2
[0462]
[0463] The steel sheet with the plated layer was temper rolled. The arithmetic mean roughness Ra (μm) and the pressing force P (t) of the temper roll used for the temper rolling are shown in Table 2. The FA value (= (CR1+CR2) / {2(Ra×P)}) is shown in Table 2.
[0464] A water-based surface treatment agent having a mixing ratio shown in Table 3 was prepared as follows. Each component shown in Table 3 was added to a certain amount of deionized water during stirring using a propeller stirrer, and the solid content concentration was prepared to be 15% by mass. The pH of the water-based surface treatment agent was adjusted to 8.0 to 11.0. Carbonic acid and / or ammonia were used as a pH adjuster for the water-based surface treatment agent.
[0465] [Table 3]
[0466] Table 3
[0467]
[0468] The types of the components shown in Table 3 were adjusted as follows.
[0469] [Acrylic resin]
[0470] The copolymers (acrylic resins) of A1 to A17 shown in Table 5 were obtained by using styrene (b1), (meth) acrylic acid (b2), (meth) alkyl ester (b3), and acrylonitrile (b4) indicated as abbreviations in Table 4 at the ratios shown in Table 5. The content of the acrylic resin in the water-based surface treatment agent in Table 3 is the mass (mass %) relative to the total solid content of the water-based surface treatment agent.
[0471] [Table 4]
[0472] Table 4
[0473]
[0474] [Table 5]
[0475] Table 5
[0476]
[0477] As the Zr compound, the V compound, the P compound, and the Co compound, the following compounds were prepared.
[0478] [Zr compounds]
[0479] As the Zr compound, the following three compounds were prepared.
[0480] B1: Potassium zirconium carbonate
[0481] B2: Ammonium zirconium carbonate
[0482] B3: Ammonium Fluozirconate
[0483] [V compound]
[0484] C1: Vanadium acetylacetonate
[0485] C2: Vanadyl Oxalate
[0486] [P compound]
[0487] D1: Phosphoric acid
[0488] D2: 1-Hydroxyethane-1,1-diphosphonic acid
[0489] [Co compounds]
[0490] E1: Cobalt carbonate
[0491] E2: Cobalt Nitrate
[0492] The steel sheets with plating layers formed on both sides of the test numbers shown in Table 1 (Table 1-1 and Table 1-2) were degreased using a degreasing agent (alkaline degreasing agent manufactured by Nippon Parkersei Co., Ltd., trade name: FINE CLEANERE 6406) (20 g / L solution, 60° C.) and then rinsed with water using a spray for 10 seconds (spray pressure 50 kPa).
[0493] The water-based surface treatment agent shown in Table 3 was applied to both sides of the steel plate having the coating layer on both sides after degreasing. Specifically, the water-based surface treatment agent was applied using a roller coater. At this time, the peripheral speed ratio of the roller coater was adjusted to adjust the film thickness of the coating film. The steel plate having the coating film formed on the coating layer was heated while supplying hot air to the coating film using a hot air circulation oven (heating furnace), so that the coating film formed on the coating layer was dried.
[0494] The surface-treated steel sheets of each test number were manufactured by the above-mentioned process. The thickness of the surface-treated steel sheets of each test number was 2.3 mm.
[0495] [Evaluation test]
[0496] The following evaluation tests were performed on the surface-treated steel sheets of the respective test numbers.
[0497] (Test 1) Chemical composition analysis test of the coating
[0498] (Test 2) Test for measuring the amount of chemical conversion film adhered
[0499] (Test 3) [V] and [P] measurement test
[0500] (Test 4) Mg concentration difference Δ[Mg] measurement test
[0501] (Test 5) Corrosion resistance evaluation test
[0502] (Test 6) Adhesion evaluation test
[0503] (Test 7) Blackening resistance evaluation test
[0504] (Test 8) Condensation resistance discoloration evaluation test
[0505] Hereinafter, Tests 1 to 8 will be described.
[0506] [(Test 1) Chemical composition analysis test of the coating]
[0507] The content (mass %) of each element in the chemical composition of the plating layer of each test number was determined based on the method described in the above-mentioned [Method for measuring the chemical composition and adhesion amount of the plating layer 20]. As a result, the chemical composition of the plating layer of each test number is as shown in Table 1 (Table 1-1 and Table 1-2).
[0508] [(Test 2) Test for measuring the amount of chemical conversion film adhered]
[0509] The amount of chemical conversion film of each test number was measured based on the method described in the above-mentioned [Method for measuring the amount of chemical conversion film 30]. The obtained results are shown in Table 6 as "Amount of chemical conversion film (mg / m 2 )"column.
[0510] [Table 6]
[0511] Table 6
[0512]
[0513] [(Test 3) [V] and [P] measurement test]
[0514] The V mass [V] (mg / m 2 ) and P mass [P] (mg / m 2). Using the obtained V mass [V] and P mass [P], F1 (= [V] / [P]) is calculated. Furthermore, using the Mg content [Mg]b of the chemical composition of the plating layer and the V mass [V], F2 (= [V] / [Mg]b) is calculated. The obtained V mass [V] (mg / m 2 )、P mass [P] (mg / m 2 ), F1 value, and F2 value are shown in Table 6.
[0515] In addition, the components of the chemical conversion film were measured based on [Method for measuring the mass of Zr, V, P and Co in the chemical conversion film 30] and [Method for confirming and measuring the content of acrylic resin in the chemical conversion film 30]. As a result, in any test number, the chemical conversion film contains Zr, V, P and Co, and acrylic resin. In addition, the Zr content (mass %), V content (mass %), P content (mass %), Co content (mass %) and acrylic resin content (mass %) in the chemical conversion film are as shown in Table 3. In addition, the content of each component in the acrylic resin in the chemical conversion film 30 was obtained based on the method described in [Method for measuring the content of each component in the acrylic resin in the chemical conversion film 30]. As a result, the content of each component of the acrylic resin is as shown in Table 5.
[0516] [(Test 4) Mg concentration difference Δ[Mg] measurement test]
[0517] The Mg concentration difference Δ[Mg] (mass %) was determined based on the method described in the [Method for determining the Mg concentration difference Δ[Mg]] above. Then, based on the obtained Mg concentration difference Δ[Mg] (mass %) and the V mass [V] (mg / m 2 ) to obtain F3 (=Δ[Mg]×[V]). The obtained Mg concentration difference Δ[Mg] (mass %) is shown in the "Δ[Mg] (mass %)" column of Table 6. Furthermore, the obtained F3 value is shown in the "F3" column of Table 6.
[0518] [(Test 5) Corrosion resistance evaluation test]
[0519] A flat test piece was collected from the surface treated steel plate of each test number. The size of the flat test piece was set to 50 mm × 100 mm × plate thickness. The flat test piece was subjected to a 240-hour salt spray test in accordance with JIS Z 2371:2015. The surface of the flat test piece after the test was observed to determine the area ratio of white rust. The area ratio of white rust obtained was evaluated as follows.
[0520] E (Excellent): The area ratio of white rust is less than 5.0%
[0521] B (Bad): The area ratio of white rust is greater than 5.0%
[0522] The obtained results are shown in the "Corrosion Resistance" column in Table 6.
[0523] [(Test 6) Adhesion evaluation test]
[0524] Two test pieces were collected from the surface treated steel plate for each test number. The dimensions of the test pieces were as follows: width: 25 mm, thickness: plate thickness, length: 100 mm.
[0525] like Figure 3 As shown, the ends of the two test pieces 100 are arranged in an overlapping manner, and the adhesive 120 is applied to the overlapping portion of the two test pieces 100. The area of the bonding portion is set to width: 25 mm × length: 12.5 mm. The adhesive used is an acrylic adhesive HARDLOC (manufactured by Denka Co., Ltd., trade name: c355-20). The two test pieces 100 are bonded together by applying the adhesive. Figure 3 After that, the backing plate 150 was placed at the end of each test piece 100 to produce a lap shear test body 200 .
[0526] A tensile shear test was performed using the produced lap shear test body. At this time, the distance between the chucks was set to 112.5 mm, and the tensile speed was set to 2 mm / min. The tensile shear load (N) was obtained by the tensile shear test under the above conditions.
[0527] Based on the obtained tensile shear load, evaluation was performed as follows.
[0528] E: tensile shear load is 5.2×10 3 N or above
[0529] B: tensile shear load is less than 5.2×10 3 N
[0530] The obtained results are shown in the "Adhesion" column in Table 6.
[0531] [(Test 7) Blackening resistance evaluation test]
[0532] A test piece of 50 mm×100 mm×plate thickness was collected from the surface treated steel plate of each test number and allowed to stand for 144 hours in an atmosphere of 70° C. and 85% relative humidity (RH) using a constant temperature and humidity testing machine.
[0533] The L is calculated for the surface of the test piece before and after the test. * value, a * value, and b *Specifically, the CIE standard light source D65 was used as the light source, the viewing angle was set to 10°, and the L was calculated using the CIELAB color system using the SCE method for the surface of the test piece before and after the test. * value, a * value, and b * The SCE method is defined in JIS Z8722:2009. * value, a * value, and b * The color difference ΔE is calculated using the following formula * .
[0534] ΔE * ={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2
[0535] ΔL * = L after test * -L before the test *
[0536] Δa * = a after the test * - Before the test *
[0537] Δb * = b after the test * -b before the test *
[0538] Among them, L before and after the test * value, a * value, and b * The values were measured using a colorimeter manufactured by Konica Minolta, Inc. (trade name: CM-2600d).
[0539] Based on the obtained ΔE * The blackening resistance was evaluated as follows.
[0540] E: ΔE * ≤3.0
[0541] B: ΔE * >3.0
[0542] The obtained results are shown in the "blackening resistance" column in Table 6.
[0543] [(Test 8) Condensation resistance discoloration evaluation test]
[0544] A 50mm×100mm×plate thickness test piece was collected from the surface treated steel plate of each test number. Six drops of pure water were dripped onto the surface of the test piece. At this time, each drop was dripped into a separate area. The test piece after dripping was placed in the atmosphere at room temperature for 12 hours to dry the water droplets. After observing the surface of the test piece after 12 hours, several discolored areas were confirmed in the 12 dripping areas. The condensation resistance was evaluated according to the number of discolored areas as follows.
[0545] E: There are 2 or fewer discolored areas.
[0546] G: There are 3 to 5 color change areas.
[0547] B: There are 6 or more discolored areas.
[0548] The obtained results are shown in the column "Resistance to discoloration due to condensation" in Table 6.
[0549] [Evaluation results]
[0550] Referring to Table 6, in the surface treated steel sheets of test numbers 1 to 44, the chemical composition of the coating is appropriate, and the chemical conversion film contains Zr, V, P and Co, and acrylic resin. In addition, the amount of chemical conversion film attached is appropriate, and F1 and F2 are also appropriate. Therefore, excellent corrosion resistance, excellent adhesion to the adhesive, and excellent blackening resistance are obtained, and excellent condensation discoloration resistance is obtained.
[0551] In particular, in the surface treated steel sheets of test numbers 1 to 35, the preferred manufacturing conditions 1 to 3 were satisfied. Therefore, F1 and F2 were appropriate, and F3 was appropriate. Therefore, compared with test numbers 36 to 44, more excellent condensation discoloration resistance was obtained.
[0552] On the other hand, in Test Nos. 45 and 46, the amount of the chemical conversion film deposited was too small, so that sufficient corrosion resistance and sufficient adhesion could not be obtained.
[0553] In test numbers 47 and 48, the amount of chemical conversion film deposited was too large, so sufficient adhesion could not be obtained.
[0554] In test numbers 49 and 50, F1 was too low, and therefore, sufficient blackening resistance could not be obtained.
[0555] In test numbers 51 and 52, F1 was too high, and therefore, sufficient corrosion resistance could not be obtained.
[0556] In test numbers 53 and 54, F2 was too high, and therefore, sufficient condensation-induced discoloration resistance could not be obtained.
[0557] In Test No. 55, the Mg content in the plating layer was low, so sufficient corrosion resistance could not be obtained.
[0558] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented within the scope of the present disclosure.
Claims
1. A surface treated steel plate comprising: Base steel plate; a coating formed on the base steel plate; and a chemical conversion film formed on the coating, The chemical composition of the coating layer contains, by mass%, Al: greater than 5.0% and less than 25.0%, Mg: more than 3.0% and less than 12.5%, Sn: 0-3.00%, Bi: 0~5.00%, In: 0~2.00%, Ca: 0-3.00%, Y:0~3.00%、 La: 0-3.00%, Ce: 0~3.00%, Si: 0-2.50%, Cr:0~0.5%、 Ti: 0-0.5%, Ni: 0-0.5%, Co: 0-0.5%, V:0~0.5%、 Nb: 0-0.5%, Cu: 0-0.5%, Mn: 0~0.5%, Fe: 0-5.0%, Sr:0~0.5%、 Sb: 0-0.5%, Pb: 0 to 0.5%, and B: 0 to 0.5%, The balance is 65.0% or more of Zn and impurities, The chemical conversion film contains: Zr, V, P and Co; and Acrylic resin, The adhesion amount of the chemical conversion film is 300 to 1000 mg / m 2 , V mass in the chemical conversion film [V] mg / m 2 and the P mass in the chemical conversion film [P] mg / m 2 Satisfying formula (1), The Mg content [Mg] b mass % and the V mass [V] mg / m 2 Satisfying formula (2), 0.60≤[V] / [P]≤2.80 (1) 0<[V] / [Mg]b≤20.00 (2).
2. The surface-treated steel sheet according to claim 1, wherein: and, The Mg concentration difference Δ[Mg] mass % and the V mass [V] mg / m , which are the difference between the Mg concentration [Mg] s mass % at the surface layer of the plating layer and the Mg content [Mg] b mass % of the chemical composition of the plating layer, obtained by elemental analysis in the depth direction of the plating layer using glow discharge emission spectrometry, are 2 Satisfying formula (3), Δ[Mg]×[V]≤200 (3).
3. The surface-treated steel sheet according to claim 1 or 2, wherein: The chemical composition of the coating layer contains, by mass%, Sn: 0.01~3.00%, Bi: 0.01~5.00%, In: 0.01~2.00%, Ca: 0.01-3.00%, Y:0.01~3.00%、 La: 0.01~3.00%, Ce: 0.01~3.00%, Si: 0.01-2.50%, Cr:0.1~0.5%、 Ti: 0.1-0.5%, Ni: 0.1-0.5%, Co: 0.1-0.5%, V:0.1~0.5%、 Nb: 0.1-0.5%, Cu: 0.1-0.5%, Mn: 0.1-0.5%, Fe: 0.1-5.0%, Sr:0.1~0.5%、 Sb: 0.1-0.5%, Pb: 0.1-0.5%, and B: One or more elements selected from the group consisting of 0.1 to 0.5%.
Citation Information
Patent Citations
Metallic surface treating agent, metallic surface treating method and surface treated metallic material
JP2002030460A
Chromate-free treated hot dip zinc - aluminum alloy plated steel sheet having excellent weldability and corrosion resistance
JP2003055777A
CHROMATE-FREE SURFACE-TREATED Al-Zn ALLOY PLATED STEEL PLATE OF EXCELLENT CORROSION RESISTANCE, WORKABILITY AND APPEARANCE QUALITY, AND METHOD FOR MANUFACTURING THE SAME
JP2005097733A
Surface treatment for metal materials, surface treatment process, and surface-treated metal materials
WO2007069783A1
Zinc-plated steel material coated with composite film excellent in corrosion resistance, unsusceptibility to blackening, coating adhesion, and alkali resistance
WO2007123276A1